THE EFFECT OF PRODUCT UTILITARIAN ON SWITCHING OF PREMIUM TO PERTALITE PRODUCTS IN BENGKALIS - Annisa April Liyani; Hutomo Atman Maulana (Politeknik Negeri Bengkalis, 2022)
This study aims to the effect of product utilitarian on switching of premium to pertalite products in Bengkalis. The independent variable is productutilitarian and the dependent variable is switching. The type of research used is associative research with a quantitative approach by collecting primary data through a survey method by distributing questionnaires to 100 consumers who have used pertalitein Bengkalis. Data processing uses the SPSS 23 application. The data analysis used is descriptive analysis, classical assumption, simple linier regression, and t-test. Based on the tests carried out, the results of this study indicate that the product utilitarian has a positive and significant effect on the switching of premium to pertalite products. The quality T value product utilitarian 11.805 which shows that utilitarian affect switching then can be seen with the analysis R square 0.587, which means that 58.7% variables of ProductUtilitariancan affect the variable of s Switching, and 41.3% Other variable that affect products switchingoutside of this study. Respondentsprefer to switch premium products to Pertalite because the quality of Pertalite is good for vehicles, it is more economical and the materials used are more environmentally friendly.